Exploring Knowledge, Attitude And Practice On Psychological Stress Among Early Childhood Teachers In Pahang - Nur Iffa Hazira, Nasaruddin (2025)
Psychological stress among early childhood teachers is an increasingly significant issue that can adversely affect their well-being and professional performance. This study aims to determine the prevalence of psychological stress, assess the levels of knowledge, attitude, and practice (KAP) related to stress, and explore the relationships between KAP and psychological stress levels as measured by the Depression, Anxiety, and Stress Scale (DASS-21). A cross-sectional study design was employed, and data were collected from a sample of 60 early childhood teachers using validated questionnaires. The results revealed that anxiety had the highest prevalence among the psychological stress indicators, affecting 40% of respondents. While knowledge and practice showed significant associations with anxiety levels where the p-value is less than 0.05, attitudes alone were not directly correlated. Teachers with higher knowledge levels and effective stress management practices were less likely to experience anxiety. These findings underscore the importance of translating knowledge into actionable practices to mitigate psychological stress effectively. The study highlights the need for targeted interventions and support systems to enhance teachers' coping strategies, ensuring their well-being and professional effectiveness.